How labor market institutions affect job creation and productivity growth - Magnus Henrekson (IZA World of Labor, 2020)
Economic growth requires factor reallocation across firms and continuous replacement of technologies. Labor market institutions influence economic dynamism by their impact on the supply of a key factor, skilled workers to new and expanding firms, and the shedding of workers from declining and failing firms. Growth-favoring labor market institutions include portable pension plans and other job tenure rights, health insurance untied to the current employer, individualized wage-setting, and public income insurance systems that encourage mobility and risk-taking in the labor market.
Keywords: H32; J63; L5; L25; M13; O31; O43; 330; entrepreneurship; gazelles; high-growth firms; innovation; labor market policy; productivity